REEdI Design Thinking for Developing Engineering Curricula - Fiona Boyle; Joseph Walsh; Daniel Riordan; Cathal Geary; Padraig Kelly; Eilish Broderick (MDPI AG, 2022)
Universities are coming under increasing pressure to re-invent the way that engineering is taught in order to produce graduates that are capable of meeting the skills needs of the country's industries. This paper described an active project where Design Thinking (DT) methodology is being applied in a novel way to Engineering Curriculum Development. Enterprise partners from a range of different manufacturing sectors participated in a series of Curriculum Development workshops and the results were cross referenced with subjects taught on existing engineering programmes internationally. This process highlighted the need for increased training in Lean, 6-Sigma, transversal and soft skills competencies, and the need to review how and when content is delivered. A survey was developed from the results of the workshops and sent out to a larger cohort of industry contacts for feedback on the proposed Engineering curriculum. Design Thinking methodology has helped ensure our customers' needs are met by building the curriculum framework around competencies identified by both industry and academia while ensuring the students engage in a significant learning experience through experiential and applied learning using the latest immersive technologies.